2020
DOI: 10.31219/osf.io/3ndhm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Processing agreement in Hindi: When agreement feeds attraction

Abstract: Previous studies have demonstrated robust agreement attraction effects in subject-verb agreement languages. It is an open question whether such attraction effects extend to languages whose agreement systems differ from this prototypical agreement pattern. To address this question, we conducted four forced-choice completion experiments investigating agreement processing in Hindi. Hindi has a mixed-agreement system, where subject-verb agreement and object-verb agreement occur in complementary structural contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…A number of previous studies in comprehension (Nicol, Forster, & Veres, 1997;Pearlmutter, Garnsey, & Bock, 1999;Wagers, Lau, & Phillips, 2009) showed that participants found sentences like (1) acceptable more often and read them faster compared to their counterparts with a singular attractor. This phenomenon, known as agreement attraction (Bock & Miller, 1991) has been attested in a number of languages, such as in Arabic (Tucker, Idrissi, & Almeida, 2015), Armenian (Avetisyan, Lago, & Vasishth, 2020), German (Lago & Felser, 2018), Hindi (Bhatia & Dillon, 2020), Serbian (Ristic, Molinaro, & Mancini, 2016), Slovak (Badecker & Kuminiak, 2007), Spanish (Lago, Shalom, Sigman, Lau, & Phillips, 2015), and recently in Turkish (Lago et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…A number of previous studies in comprehension (Nicol, Forster, & Veres, 1997;Pearlmutter, Garnsey, & Bock, 1999;Wagers, Lau, & Phillips, 2009) showed that participants found sentences like (1) acceptable more often and read them faster compared to their counterparts with a singular attractor. This phenomenon, known as agreement attraction (Bock & Miller, 1991) has been attested in a number of languages, such as in Arabic (Tucker, Idrissi, & Almeida, 2015), Armenian (Avetisyan, Lago, & Vasishth, 2020), German (Lago & Felser, 2018), Hindi (Bhatia & Dillon, 2020), Serbian (Ristic, Molinaro, & Mancini, 2016), Slovak (Badecker & Kuminiak, 2007), Spanish (Lago, Shalom, Sigman, Lau, & Phillips, 2015), and recently in Turkish (Lago et al, 2019).…”
Section: Introductionmentioning
confidence: 91%